Self-Assembling Multifunctional Peptide Dimers for Gene Delivery Systems - Kitae Ryu; Gyeong Jin Lee; Ji-yeong Choi; Taewan Kim; Tae-il Kim (Advances in Materials Science and Engineering)
Self-assembling multifunctional peptide was designed for gene delivery systems. The multifunctional peptide (MP) consists of cellular penetrating peptide moiety (R8), matrix metalloproteinase-2 (MMP-2) specific sequence (GPLGV), pH-responsive moiety (H5), and hydrophobic moiety (palmitic acid) (CR8GPLGVH5-Pal). MP was oxidized to form multifunctional peptide dimer (MPD) by DMSO oxidation of thiols in terminal cysteine residues. MPD could condense pDNA successfully at a weight ratio of 5. MPD itself could self-assemble into submicron micelle particles via hydrophobic interaction, of which critical micelle concentration is about 0.01 mM. MPD showed concentration-dependent but low cytotoxicity in comparison with PEI25k. MPD polyplexes showed low transfection efficiency in HEK293 cells expressing low level of MMP-2 but high transfection efficiency in A549 and C2C12 cells expressing high level of MMP-2, meaning the enhanced transfection efficiency probably due to MMP-induced structural change of polyplexes. Bafilomycin A1-treated transfection results suggest that the transfection of MPD is mediated via endosomal escape by endosome buffering ability. These results show the potential of MPD for MMP-2 targeted gene delivery systems due to its multifunctionality.